The effect of 3-nitropropionic acid on behavioral dysfunction, neuron loss and gliosis in the brain of adult male rats: The case of prefrontal cortex, hippocampus and the cerebellum. (August 2020) - Torabi, Abolfazl; Joneidi, Mohammadjavad; Mohammadzadeh, Ibrahim; Abdollahifar, Mohammad-amin; Khatmi, Aysan; Ezi, Samira; Moghaddam, Meysam Hassani; Rafiei, Romina; Kahrizirad, Farshad; Norozian, Mohsen; Aliaghaei, Abbas
Abstract: 3-nitropropionic acid (3-NP) is a mycotoxin widely used to produce a rat model of Huntington's disease. While there are numerous studies on the effect of this neurotoxin, still further investigation is required to understand the influence of this toxin on different regions of the brain. In the present study, there are two groups of rats of which one is treated with 3-NP. Behavioral, stereological and immunohistochemical analyses were conducted. The results show that locomotor activity is largely affected and anxiety is induced up to a certain level, but there is no gross manifestation of deficit in memory. Microscopic observations illustrate damages in the hippocampus and other parts of the brain. Astrogliosis and glial scars were another finding of this study. In conclusion, although 3-NP can be used as a model of Huntington's disease, it exerts a disseminated effect on different regions of the brain. Graphical abstract: Image 1 Highlights: 3-Nitropropionic acid administration increased anxiety-related behaviors. 3-Nitropropionic acid administration decreased locomotor activity. 3-Nitropropionic acid administration did not affect spatial working memory. 3-Nitropropionic acid administration increased neuronal loss and astrogliosis.